2015
DOI: 10.2214/ajr.14.13835
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Model-Based Iterative Reconstruction on CT Number Measurements Within Small (10–29 mm) Low-Attenuation Renal Masses

Abstract: Veo MBIR has no significant or consistent effect on attenuation measurements within small (10-29 mm) low-attenuation renal masses and is therefore unlikely to change clinically accepted attenuation thresholds for renal mass characterization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…Our study found no significant difference in mean attenuation between different image sets. This has also been demonstrated in prior studies comparing Veo 3.0 to FBP, ASIR and Veo 2.0, 20,24 supporting maintained accuracy of MBIR CT attenuation for lesion characterization even when performed with different noise reduction and resolution preference presets.…”
supporting
confidence: 75%
“…Our study found no significant difference in mean attenuation between different image sets. This has also been demonstrated in prior studies comparing Veo 3.0 to FBP, ASIR and Veo 2.0, 20,24 supporting maintained accuracy of MBIR CT attenuation for lesion characterization even when performed with different noise reduction and resolution preference presets.…”
supporting
confidence: 75%
“…26 Presently, the ASiR technique has become a routine clinical practice instead of the conventional filtered back projection algorithm. Based on the recommendations of the manufacturer and our practical experience, ASiR weighting was set at 30% in the conventional 120-kVp CT and monochromatic spectral image at 69 keV level; moreover, 50% ASiR weighting in monochromatic spectral image at 52 keV level was based on previous study 17,27 and the current phantom experiment. Low monochromatic energy images coupled with 50% ASiR weighting can effectively suppress the increased image noise due to the lack of photon flux.…”
Section: Bjrmentioning
confidence: 99%